Comparative Analysis of Measures and Technical Means for Suppressing the Aperiodic Current Component in Circuit Breaker - V. V. Kuchanskyi (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Electromagnetic transients are considered in the implementation of three-phase automatic reclose on the transmission line of extra high voltage 750 kV. The influence of automatic shunting of phases and pre-insertion active resistance for limiting the characteristics of the aperiodic component of the current, which obstructs the transition of full current through zero, is evaluated. The paper analyses measures taking into account the effect of changing the degree of compensation of charging power and the angles of switching on an SF6 circuit breaker. Sub-schemes of disconnected undamaged phases of the extra high voltage transmission line for the investigation of the aperiodic current component have been developed. The values of the pre-insertion active resistances of different connection and automatic shunting of the phases are determined at which there is an effective reduction of the characteristics of the aperiodic component of the current. In the software environment, a model was developed and switching transient processes were simulated in the 750 kV transmission line. Operating modes that are potentially dangerous for SF6 circuit breakers are determined and recommendations are given to avoid them. Currently the technical and economic requirements for power transmission lines designed for the transport of electricity from large power plants and for the communication of powerful energy systems are increasing. Today there is the importance of reducing specific investment in the construction of new and reconstruction of existing lines. The solution of these issues is associated with the maximum use of power lines by increasing their power transfer capability and controlling modes, especially in operating emergency conditions and post-emergency operation of power systems.